2020
DOI: 10.5009/gnl19237
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Diagnosis of Nonpedunculated Dysplasia during Surveillance of Ulcerative Colitis: A Survey-Based Multinational Study

Abstract: Background/Aims: Endoscopic diagnosis of dysplasia or colitic cancer in patients with ulcerative colitis (UC) is more challenging than that of colorectal neoplasia in non-colitic patients. We aimed to evaluate the accuracy of the endoscopic diagnosis of "nonpedunculated" dysplasia or colitic cancer in UC patients. Methods: Ten endoscopists from four countries were surveyed using photographs of 61 histologically confirmed dysplastic or non-dysplastic lesions retrieved from the UC registry database of Asan Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Ulcerative colitis (UC) is a chronic inflammatory disease of the colon caused by unbalanced immune responses to host intestinal microbiota and main threatens to public health ( Roselli and Finamore, 2019 ). Although much progress has been made in diagnosis ( Yang et al., 2019 ; Vadstrup et al., 2020 ) and therapy ( Karjalainen et al., 2020 ; Kunovszki et al., 2020 ) for UC in recent years, an effective therapeutic drug is still difficult to be available. Gut microbiota disturbance ( Noor et al., 2010 ) and intestinal barrier injury ( Chen et al., 2019 ) is often associated with a UC risk.…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is a chronic inflammatory disease of the colon caused by unbalanced immune responses to host intestinal microbiota and main threatens to public health ( Roselli and Finamore, 2019 ). Although much progress has been made in diagnosis ( Yang et al., 2019 ; Vadstrup et al., 2020 ) and therapy ( Karjalainen et al., 2020 ; Kunovszki et al., 2020 ) for UC in recent years, an effective therapeutic drug is still difficult to be available. Gut microbiota disturbance ( Noor et al., 2010 ) and intestinal barrier injury ( Chen et al., 2019 ) is often associated with a UC risk.…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate technical barriers to magnifying endoscopes and effectively introduce the pit pattern into clinical practice, the usefulness of pit pattern evaluation in non magnified settings has been assessed. Three studies examined the feasibility of using the pit pattern without magnification to differentiate neoplastic from non‐neoplastic lesions 24,26,39 . These studies showed that with the non magnification setting, the sensitivity was lower than, and specificity was comparable to, that of the magnification setting: the sensitivity ranged from 68% to 77%, and the specificity ranged from 63% to 90%.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement of the interobserver agreement rates is also important for widespread use of diagnostics. The interobserver agreement regarding the intention to perform biopsy (Fleiss' kappa of 0.17) 39 and the overall interobserver agreement for any pit pattern (Fleiss' kappa of 0.28) 26 are reportedly poor to fair.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, targeted biopsy may be cost-effective and time-saving [20]. An inter-observer agreement study has shown poor agreement on intention to biopsy among endoscopists in non-pedunculated potentially dysplastic lesions in UC [21]. Apart from IEE, EUS-guided assessment of depth of invasion can help in treatment selection [22].…”
Section: Detection Of Ucanmentioning
confidence: 99%